Assessment of Vulnerability for Land Degradation - Purevee, Sodgerel sodoo (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
Many scientists agreed that land degradation is caused by multiple forces, including extreme weather conditions particularly drought, and human activities that overgrazing in Mongolia. Geographic information system (GIS) have an important role in linkage and analysis of all aspects, in particular for determine land degradation risk. This paper describes four risk performance indicators and their attribute data tables of air temperature, rainfall, carrying capacity, road density were compiled into the digital geomorphologic map units in a geographic information system. As result this study, the very high-risk area was present in 0,03% and moderate hazardous area was 52,6 %, low risk area was 47.3%.